แนวคิดในการร่างรัฐธรรมนูญของไทย : ศึกษากรณีรัฐธรรมนูญ ฉบับปีพุทธศักราช 2511, 2517 และ 2540 - ถาวร ฤทัยวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The objectives for a study of "ideas in drafting of constitution in Thailand : a case study of constitutional in 1968, 1974 and 1997" are to find both concept, origin and evolution of constitutional drafting and form, structure and power of the mentioned constitutions. The hypothesis of the study is "ideas in drafting constitution of the kingdom of Thailand B.E. 1997 are evolved to be more democratic according to the society change." The results of the study found that the constitutional drafting assembly for the constitution B.E. 1968, which nost of the members appointed by the revolution party, are quite lack of freedom. Although some articles in the constitution of the kingdom of Thailand B.E. 2489 such as form of parliamentary system, guaranty on freedom of the people are enacted in this constitution but, on the otherhand, some principles of the revolution party are also enacted together. The constitutinal drafting assembly for the constitution B.E. 1974, Which all of member appointed by Mr Sanya Thammasakdi, got a lot of freedom in drafting process, moreover the people are take part in public hearings process. The constitution of the kingdom of Thailand B.E. 1974 has a democratic value and also a constitution for the people. The constitutional drafting assembly for the constitution B.E. 1997, which the member are elected by the Senators and the member of the House of Representatives and the people from all folks of life participated in legislative process. Hence, the origin of an organization or the people who take part in drafting process are so significant since it indicates the basic, free will and evolution of democratic for each constitution. Moreover, an evolution of each constitutions depends upon social pressure.